Confidence‐competence alignment and the role of self‐confidence in medical education: A conceptual review. Issue 1 (20th July 2021) - Gottlieb, Michael; Chan, Teresa M.; Zaver, Fareen; Ellaway, Rachel
Abstract: Context: There have been significant advances in competency‐based medical education (CBME) within health professions education. While most of the efforts have focused on competency, less attention has been paid to the role of confidence as a factor in preparing for practice. This paper seeks to address this deficit by exploring the role of confidence and the calibration of confidence with regard to competence. Methods: This paper presents a conceptual review of confidence and the calibration of confidence in different medical education contexts. Building from an initial literature review, the authors engaged in iterative discussions exploring divergent and convergent perspectives, which were then supplemented with targeted literature reviews. Finally, a stakeholder consultation was conducted to situate and validate the provisional findings. Results: A series of axioms were developed to guide perceptions and responses to different states of confidence in health professionals: (a) confidence can shape how we act and is optimised when it closely corresponds to reality; (b) self‐confidence is task‐specific, but also inextricably influenced by the individual self‐conceptualisation, the surrounding system and society; (c) confidence is shaped by many external factors and the context of the situation; (d) confidence must be considered in conjunction with competence and (e) the confidence‐competence ratio (CCR) changes over time. It is important to track learners' CCRs and work with them to maintain balance. Conclusion: Confidence is expressed in different ways and is shaped by a variety of modifiers. While CBME primarily focuses on competency, proportional confidence is an integral component in ensuring safe and professional practice. As such, it is important to consider both confidence and competence, as well as their relationship in CBME. The CCR can serve as a key construct in developing mindful and capable health professionals. Future research should evaluate strategies for assessing CCR, identify best practices for teaching confidence and guiding self‐calibration of CCR and explore the role of CCR in continuing professional development for individuals and teams. Abstract : @MGottliebMD @TChanMD @fzaver @drellaway review the concepts of confidence, competence, and the intersectionality between the two in this 'State of the Science' paper on "Self" in medical education.